Some facts which suggest the idea that the desire for alcoholic stimulants is not only transmitted by hereditary descent, but that it is also felt with increasing force from generation to generation, and thus strongly tends to deteriorate the human race - Haughton, James (Dublin Statistical Society, 1858)
My object will be attained if I shall have awakened this new idea in any of your minds, so that it may lead to a further and more searching investigation of this important question. For surely it will be considered by all a matter of no light importance, to ascertain whether, in indulging our propensity for alcoholic stimulants, we may not be handing down to our children the seeds of fierce desire, which will, almost of necessity, hurry them in a career of vice and crime, and cause them to transmit to their successors, in accumulating force, those influences which lead to a rapid deterioration of our race.
Read 15th February, 1858
Keywords: Alcoholism, Hereditary aspects; Intemperance; 314.15